2006
DOI: 10.1074/jbc.m601714200
|View full text |Cite
|
Sign up to set email alerts
|

Siglec-7 Undergoes a Major Conformational Change When Complexed with the α(2,8)-Disialylganglioside GT1b

Abstract: The siglecs are a group of mammalian sialic acid binding receptors expressed predominantly in the immune system. The CD33-related siglecs show complex recognition patterns for sialylated glycans. Siglec-7 shows a preference for ␣(2,8)-disialylated ligands and provides a structural template for studying the key interactions that drive this selectivity. We have co-crystallized Siglec-7 with a synthetic oligosaccharide corresponding to the ␣(2,8)-disialylated ganglioside GT1b. The crystal structure of the complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 60 publications
3
83
0
Order By: Relevance
“…A common feature of the binding surface and a notable contribution to its energy is provided by CH-stacking of sugar rings and aromatic protein sidechains (38). Examples most relevant to this study include clostridial neurotoxin in complex with GD1 sugar (39) and sialic acid receptor of immune cells (siglec-7) in complex with GT1b analog (40). In both structures the ganglioside is recognized in a relatively shallow hollow compared with the pronounced groove found in 14G2a.…”
Section: Discussionmentioning
confidence: 99%
“…A common feature of the binding surface and a notable contribution to its energy is provided by CH-stacking of sugar rings and aromatic protein sidechains (38). Examples most relevant to this study include clostridial neurotoxin in complex with GD1 sugar (39) and sialic acid receptor of immune cells (siglec-7) in complex with GT1b analog (40). In both structures the ganglioside is recognized in a relatively shallow hollow compared with the pronounced groove found in 14G2a.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro-binding studies have revealed that siglec-7 shows a marked preference for glycoconjugates bearing ␣(2,8)-linked disialic acid (GD3 and GT1b) and branched ␣(2,6)-linked sialic acid (69). The function of siglec-7 on NK cells appear to be related with a down-modulation of the NK killing activity (70), therefore trans interactions between NK cells and DC could serve this function.…”
Section: Discussionmentioning
confidence: 99%
“…However, Arg-118, which forms an important salt bridge with the negatively charged carboxyl group of SA, is conserved among other Siglec family molecules. The structures of other Siglec family molecules suggest that Arg-118 in MAG is directly involved in binding to SAs (11,12,(47)(48)(49)(50)(51)(52)(53)(54). Therefore, mutation in Arg-118 in MAG seems to have affected the association with SAs rather than the conformation of MAG.…”
Section: Discussionmentioning
confidence: 99%